Introduction to GIS Application in the Land Cadastre - Ibragimov L.T; Tojidinova F.M; Raximov B.A (Research Parks Publishers, 2022)
This article addresses the problems with maintaining a land cadastre related to the processing of data on cadastre objects and discusses the current state of GIS technology. The fundamental tenets of contemporary GIS technology in land cadastre management are presented. The contemporary system of land use is categorized. Consideration is given to creative schemes for keeping the state land cadastre up to date.